HIV-1 transmitted drug resistance in latin America and the Caribbean: What do we know? (2012)
Latin America and the Caribbean countries have increased the scaling-up of antiretroviral treatment in the last years. The increase of transmitted drug resistance has been feared due to the worrisome indicators associated with the emergence of drug resistance and monitored by the World Health Organization (WHO). Consequently, our aim was to review all relevant studies on transmitted drug resistance in Latin America and the Caribbean countries, to analyze its levels, to identify the frequency of transmitted drug resistance mutations, and to put these results in the context of the local Latin American and Caribbean countries settings. A systematic search of Spanish, Portuguese, and English literature was performed in databases and international conferences for the period June 1999 to May 2011. In addition, sequences were downloaded from the Los Alamos and Stanford databases and the transmitted drug resistance was reanalyzed according to the WHO Surveillance Drug Resistance Mutation list 2009. In total, 50 articles, 27 abstracts, and 1,922 patients were included. The resistance varied geographically, but most of the countries have reached the WHO threshold of 5% of resistance. According to the sequences available in public databases, the overall prevalence in Latin America and the Caribbean countries for the period 1996-2009 was 7.7% and by region it was 4.3% for the Caribbean, 3.9% for Mexico, 9.4% for Brazil, 10.5% for the Andean region and 4.9% for the Southern Cone. For the last four investigated years (2006-2009), the information was restricted to Brazilian and Venezuelan studies and revealed an overall transmitted drug resistance of 10%. Throughout the study period, limited information was available for the Caribbean and Central American countries. These findings support the need for developing comprehensive surveys of transmitted drug resistance in these regions.